1986
DOI: 10.1007/bf02143054
|View full text |Cite
|
Sign up to set email alerts
|

Pars plana vitrectomy in aphakic and pseudophakic retinal detachment

Abstract: Eighty-two consecutive aphakic or pseudophakic retinal detachments were treated by buckling and vitrectomy procedures. Functional results (86.6%) and the incidence of proliferative vitreoretinopathy (11%) were comparable with reports of cases treated by the classic method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 5 publications
1
8
0
1
Order By: Relevance
“…Neverthe less postoperative aggravation of PVR was a problem, especially in grade B cases, an obser vation which agrees well with previously pub lished findings [20], To the best of our knowl edge, it has not been demonstrated that vit rectomy can reduce the risk of PVR aggravation [21], and it is even possible that it might increase it [22].…”
Section: Discussionsupporting
confidence: 78%
“…Neverthe less postoperative aggravation of PVR was a problem, especially in grade B cases, an obser vation which agrees well with previously pub lished findings [20], To the best of our knowl edge, it has not been demonstrated that vit rectomy can reduce the risk of PVR aggravation [21], and it is even possible that it might increase it [22].…”
Section: Discussionsupporting
confidence: 78%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19] In the 10 eyes requiring more than one surgery, 9 were macula-off at presentation (90%). Average preoperative VA in these eyes was 1.91.…”
Section: Resultsmentioning
confidence: 98%
“…A review of the current literature disclosed more than 20 series of primary vitrectomy for RRD in which the indications for vitrectomy are similar to the inclusion criteria of the SPR Study [3,8,9,10,13,14,15,16,19,20,21,22,23,25,31,32,33,39,41,44,45]. The reattachment rates with one operation vary between 64% [21] and 100% [9,14].…”
Section: Discussionmentioning
confidence: 98%
“…For example, primary vitrectomy followed by additional scleral buckling was either never used at all [8,10,21,23], was performed in some or selected cases [9,19,20,31,32] or was applied in all cases [3,14,41,44,45]. It is unclear whether scleral buckling plus primary vitrectomy increases the success rate or adds further complications to the procedure, as comparable success rates have been achieved with and without scleral buckling.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation